Metode Pengajaran Guru untuk Genarasi Z di Era Society 5.0 pada Mata Pelajaran Fiqih di Madrasah Aliyah Palembang - Imam Tauhid; Agra Dwi Saputra; Meddya Boty (Cendekia, 2024)
Determining teaching methods is very important, because the success or failure of achieving teaching objectives depends on how the teaching and learning process is structured and carried out effectively and efficiently. This research aims to determine and analyze the process of implementing teaching methods with students' perceptions of the methods used by fiqh subject teachers at Madrasah Aliyah Negeri 2 Palembang. This research approach uses a qualitative approach with a case study type. The population and sample of this research is one fiqh teacher and 4 students of Madrasah Aliyah Negeri 2 Palembang. 2 students consisting of 1 male, 1 female from class IX IPA 5, 2 students consisting of 1 male and 1 female student from class IX IPS 2. Data collection techniques are observation, interviews and documentation. The results of this research show that teachers' teaching methods have an important role in creating effective and enjoyable learning experiences for students. Varied and innovative methods, such as those used by a teacher at MAN 2 Palembang, can increase student enthusiasm and creativity. However, several obstacles arise, especially related to the limitations of learning media, especially in the context of online learning. Solutions to improve the quality of learning include forming teacher deliberation groups, discussions between teachers, regular training, and improvements to technological infrastructure.